The impact of care experience prior to commencing pre-registration nurse education and training: A scoping review. (January 2023) - Field-Richards, Sarah E.; Aubeeluck, Aimee; Callaghan, Patrick; Keeley, Philip; Redsell, Sarah A.; Spiby, Helen; Stacey, Gemma; Lymn, Joanne S.
Abstract: Objectives: Compassion in nursing and interventions to support it are of international relevance and concern. Prior care experience as a prerequisite for entry into pre-registration nurse education is suggested as a means of improving compassion. The impact of prior care experience has not been comprehensively reviewed, therefore the potential effectiveness of prior care experience as a means of improving compassion is unknown. The scoping review question was 'What is known about the impact of care experience prior to commencing pre-registration nurse education and training?' The primary objective was to scope and synthesise existing literature relating to the topic and ascertain key themes pertaining to impact. A secondary objective was to appraise literature, to contextualise findings and assess the state and stage of knowledge and research in the area. Design: The review was guided by Arksey and O'Malley's methodological framework and is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews Checklist. Data sources: Health sciences databases CINAHL, Medline and PubMed. Methods: Databases were searched in February 2019, updated August 2021. Data (study characteristics, findings, methodological observations) were extracted from papers meeting inclusion criteria (including peer-reviewed empirical papers with English language, electronic full-text available) and findings thematically analysed. Results: Forty-five papers from 14 countries were included. The majority (64.4 %) were published in Europe (31.1 % in the United Kingdom) between 2010 and 2021 (69 %), 60 % from 2013. Four qualitative themes (compassionate care, commitment, competence and communication) describe the impact of prior care experience, which was variable. Conclusions: Evidence to support the effectiveness of prior care experience as a prerequisite for entry into nurse education to improve compassion, is inconsistent and insufficient. The literature displays methodological limitations and conclusions should be interpreted in light of these caveats. Recommendations are made for future research, to improve quality and comparability. Highlights: An international emphasis on prior care experience after Francis (2013) is evident. Impact on compassionate care, commitment, competence, communication is documented. The nature of the impact of prior care experience is mixed and variable. There is insufficient support for improving compassion via prior care experience. The evidence base is underdeveloped and displays methodological limitations.